Oxidized and Non-Oxidized Multiwalled Carbon Nanotubes as Materials for Adsorption of Lanthanum(III) Aqueous Solutions - Francisco J. Alguacil; Irene García-Díaz; Esther Escudero Baquero; Olga Rodríguez Largo; Félix A. López (Metals, 2020)
The behavior of oxidized and non-oxidized multiwalled carbon nanotubes (MWCNTs) in the adsorption of lanthanum(III) from aqueous solutions is described. Metal uptake is studied as a function of several variables such as the stirring speed of the system, pH of the aqueous solution and metal and nanomaterial concentrations. The experimental results are fitted to various kinetic and isotherm models, the rate law being fitted to the film diffusion and particle diffusion models, when the non-oxidized and the oxidized nanomaterials are used to remove lanthanum from the solution, respectively. Sulfuric acid solutions seem to be appropriate to recover the metal from La-loaded nanomaterials.